2003
DOI: 10.1023/a:1021853302033
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Risk Perception and Psychological Morbidity in Women with Ductal Carcinoma in situ and Early Invasive Breast Cancer

Abstract: Despite the excellent prognosis, women with DCIS express serious concerns and report similar psychological morbidity as women with invasive cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
124
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(137 citation statements)
references
References 23 publications
13
124
0
Order By: Relevance
“…In spite of the relatively good prognosis, women's accounts reveal that for some, the experience is distressing and the implications are long-term, resulting in personal difficulties 'moving on' from the experience. The findings support the growing evidence that DCIS patients do not face 'less' distress (Rakovitch et al, 2003) but encounter different stress and emotions compared with those diagnosed with invasive breast cancer (Wellisch, 1997). This study identified a number of key issues which should be recognised and could inform future care and support in order to help DCIS patients adjust following the diagnosis and treatment.…”
Section: Discussion and Implications For Nursingsupporting
confidence: 81%
See 1 more Smart Citation
“…In spite of the relatively good prognosis, women's accounts reveal that for some, the experience is distressing and the implications are long-term, resulting in personal difficulties 'moving on' from the experience. The findings support the growing evidence that DCIS patients do not face 'less' distress (Rakovitch et al, 2003) but encounter different stress and emotions compared with those diagnosed with invasive breast cancer (Wellisch, 1997). This study identified a number of key issues which should be recognised and could inform future care and support in order to help DCIS patients adjust following the diagnosis and treatment.…”
Section: Discussion and Implications For Nursingsupporting
confidence: 81%
“…Anecdotal reports propose that the favourable prognosis should result in lower levels of psychosocial concerns (Hoffman, 1997). However, Rakovitch et al (2003) found that despite the generally positive outlook, DCIS patients expressed serious concerns and similar psychological morbidity to patients with invasive breast cancer. Research also suggests that women are confused about DCIS (De Morgan et al, 2002), have deficient knowledge about the condition and worry about their future cancer risk (Bluman et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Anxiety, fear, depression and uncertainty are prevalent at diagnosis (Northouse, 1992;Spiegel, 1996Spiegel, , 1997Stark and House, 2000;Witek-Janusek, et al, 2007) and distress typically intensifies with treatment burden (Berger, 1998;Berger, et al, 2007;Maraste et al, 1992;Nail and Winningham, 1995;Schreier and Williams, 2004;Theobald, 2004). The emotional response to breast cancer is independent of disease stage, as women diagnosed with non-invasive breast cancers also experience powerful emotions (Witek-Janusek, et al, 2007;Northouse, 1992;Rakovitch, et al, 2003). The emotional impact of a cancer diagnosis and the rigors of cancer treatment adversely affect quality of life (QOL) and this may persist beyond treatment (Longman, et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A Canadian study reported similar levels of anxiety and depression in women with early-stage invasive breast cancer and those with DCIS. No differences were found between the two groups regarding perceptions of the risk of developing local recurrence, distant recurrence, or breast cancer death [15]. In a Dutch study, HRQoL was compared between women with DCIS and those with early-stage invasive breast cancer [16].…”
Section: Introductionmentioning
confidence: 99%